2013
DOI: 10.1177/1721727x1301100312
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombomodulin Gene Polymorphism (C1418T) is Associated with the Development of Coronary Allograft Vasculopathy

Abstract: The first two authors contributed equal to this work Thrombomodulin (TM) is the endothelial cell membrane-bound anticoagulant protein cofactor in the thrombin-mediated activation of protein C. Previous evidence has been reported regarding the association between TM polymorphisms and coronary artery disease. Allograft rejection-mediated vasculopathy is the main cause of death at more than one year after heart transplantation. However, whether TM polymorphism is associated with allograft rejection is still uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Additionally, the transgenic expression of human TM has anti-coagulant and anti-inflammatory effects, resulting in the protection of allografts [ 18 ]; plasma-soluble TM levels are elevated in patients who have undergone hemodialysis, while levels are significantly decreased after kidney transplantation. Recently, although we have previously demonstrated that the blood levels of TM are not associated with the occurrence of vasculopathy, a correlation between the TM C1418T polymorphism and the development of vasculopathy after heart transplantation was observed [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the transgenic expression of human TM has anti-coagulant and anti-inflammatory effects, resulting in the protection of allografts [ 18 ]; plasma-soluble TM levels are elevated in patients who have undergone hemodialysis, while levels are significantly decreased after kidney transplantation. Recently, although we have previously demonstrated that the blood levels of TM are not associated with the occurrence of vasculopathy, a correlation between the TM C1418T polymorphism and the development of vasculopathy after heart transplantation was observed [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgo biloba L. leaf extracts (GBE) is one of the top selling phytopharmaceuticals in the US and Europe [4] , which are widely used for treating cerebral insufficiency, fighting memory loss and as a potential drug for Alzheimer's disease [5] . According to the German Commission E, the extracts are standardized to 24% flavone glycosides and 6% terpene lactones.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts from ginkgo leaf are widely used for treating cerebral insufficiency, fighting memory loss and as a potential drug for Alzheimer's disease [2]. The major components in Ginkgo biloba are flavonoids such as quercetin, kaempferol, rutin, and isorhamnetin [3]. The function of flavonoids such as quercetin and kaempferol is mediated by interaction with Type 2 estrogen receptors.…”
Section: Introductionmentioning
confidence: 99%